2005
DOI: 10.1038/sj.npp.1300986
|View full text |Cite
|
Sign up to set email alerts
|

Lobar Distribution of Lesion Volumes in Late-Life Depression: The Biomedical Informatics Research Network (BIRN)

Abstract: White matter hyperintense lesions on T2-weighted images are associated with late-life depression. Little work has been carried out examining differences in lesion location between elderly individuals with and without depression. In contrast to previous studies examining total brain white matter lesion volume, this study examined lobar differences in white matter lesion volumes derived from brain magnetic resonance imaging. This study examined 49 subjects with a DSM-IV diagnosis of major depression and 50 compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…Consistent with this, several studies have observed a strong association between WMHs occurring in the orbitofrontal cortex and presence of LLD 53 54 5658. However, the majority of studies of LLD employ rating scales that fail to incorporate lesion lateralisation or site.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Consistent with this, several studies have observed a strong association between WMHs occurring in the orbitofrontal cortex and presence of LLD 53 54 5658. However, the majority of studies of LLD employ rating scales that fail to incorporate lesion lateralisation or site.…”
Section: Discussionmentioning
confidence: 77%
“…Longitudinal studies are needed in order to clarify the mechanism underlying the link between hyperintensities and geriatric depression. This is an exciting avenue for future research, particularly when employing advanced imaging techniques, such as diffusion tensor imaging52 6266 which is superior at assessing white matter integrity and detecting sites where hyperintensities may directly predispose to the development of depression 18 53. Delineation of the underlying mechanisms may have an impact on how we approach prevention and treatment of LOD and may lead to novel strategies aimed at managing geriatric depression 6…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 99%
“…52 Many studies have shown that the WMH associations with LLD occur mainly in subcortical regions and their frontal white matter projections. 44,[53][54][55][56] Diffusion tensor imaging studies have also shown microstructural white matter abnormalities in fronto-striatal-limbic networks, including the lateral to anterior and posterior cingulate cortices and the prefrontal, insular and parahippocampal regions, are associated with executive dysfunction in patients with LLD. 46,57 A grey matter volume increase was observed in the right lingual gyrus both in the pooled meta-analysis and the subgroup meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, when compared to non-depressed elderly people, depressed elderly people are found to have lower frontal volumes and greater whole-brain high-intensity lesions (Kumar, Bilker, Jin, & Udupa, 2000). MacFall et al (2006) found that not only are frontal lobe lesion volumes greater in depressed elderly people, but there is also a trend for total and right parietal regions. Previous findings have also implicated frontal and parietal lesions, which extended into the occipital and temporal lobes in older individuals with greater levels of clinical depression, later onset of depression, and medical comorbidity (Artero et al, 2004).…”
Section: Neuroanatomical and Neuropsychological Findings In Late-lifementioning
confidence: 97%